Diel soundscape patterns as a potential indicator of mangrove health in Peninsular Malaysia - Chong, Leong; Jamaludin, Nurhaidah; Zakaria, Mohamed (Forestry Department of Peninsular Malaysia, 2024)
Mangrove forests are critical ecosystems that require conservation and restoration efforts to mitigate global logging trends, shoreline ingression and sea level rise. Using bioacoustic approach, this study assessed the diel acoustic patterns of four mangroves of varying ages, size and habitat gradients in Selangor, Peninsular Malaysia. Twenty bioacoustic audio recorders were set up in Telok Gong, Kapar Tambahan, Banjar Utara Forest Reserves, and Kuala Selangor Nature Park, for 30 min at each hour for 24 hours and seven days, to collect acoustic data of these soundscapes. Almost all the measured acoustic indices, especially Acoustic Complexity, Acoustic Diversity, and Normalized Difference Soundscape Indices, exhibited similar temporal patterns with a peak at the beginning of dawn and dusk. Differences in soundscapes among the study sites may potentially reflect the conditions of the mangroves which requires further investigation. Through bioacoustics approach, this study demonstrated the potential of using acoustic indices as indicators of mangrove health which may aid in monitoring the success or progress of mangrove restoration projects in the future.